UPAYA MENINGKATKAN HASIL BELAJAR BOLA VOLI MELALUI MODIFIKASI BOLA VOLI MINI PADA SISWA KELAS VI SDN 3 SELAT HULU TAHUN PELAJARAN 2020/2021 - Tri Astuti (ITB AAS Indonesia Surakarta, 2022)
Learning Physical Education, Sports and Health which is often not in accordance with the characteristics of students makes children's creativity to be neglected and learning outcomes are less than optimal. So it is necessary to modify the actual learning media. The problem and this research is